2003
DOI: 10.1038/sj.npp.1300163
|View full text |Cite
|
Sign up to set email alerts
|

Combined β-Adrenergic and Cholinergic Antagonism Produces Behavioral and Cognitive Impairments in the Water Maze: Implications for Alzheimer Disease and Pharmacotherapy with β-Adrenergic Antagonists

Abstract: This study examined the effects of b-adrenergic and muscarinic blockade on spatial learning and strategy use in the water maze. Male Long-Evans rats received systemic injections of propranolol (PRO; 10 or 20 mg/kg) or scopolamine (SCO; 0.3 or 1.0 mg/kg) either singly or in combination. To separate strategies learning from spatial learning approximately half of the rats underwent water maze strategies pretraining prior to drug administration and spatial training. PRO did not impair performance in any group. SCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 49 publications
(120 reference statements)
5
20
0
Order By: Relevance
“…The findings also suggest a link between the cognitive and behavioral impairments that occur in Alzheimer disease and the fact that multiple neurotransmitter systems such as cholinergic, noradrenergic, and serotonergic systems are typically impaired in the brain of Alzheimer patients (Chen et al, 2000;Davis et al, 1999;Dringenberg, 2000;Francis et al, 1999;Lai et al, 2002;Reinikainen et al, 1990). Our previous studies confirmed that neither PRO nor pCPA given individually impaired WM performance, and that scopolamine impaired naive but not WM strategiespretrained rats (Beiko et al, 1997;Saber and Cain, 2003). We also found that combinations of either PRO and scopolamine, or pCPA and scopolamine impaired all aspects of WM performance in both naive and strategiespretrained rats, and also caused sensorimotor impairments (Beiko et al, 1997;Saber and Cain, 2003).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…The findings also suggest a link between the cognitive and behavioral impairments that occur in Alzheimer disease and the fact that multiple neurotransmitter systems such as cholinergic, noradrenergic, and serotonergic systems are typically impaired in the brain of Alzheimer patients (Chen et al, 2000;Davis et al, 1999;Dringenberg, 2000;Francis et al, 1999;Lai et al, 2002;Reinikainen et al, 1990). Our previous studies confirmed that neither PRO nor pCPA given individually impaired WM performance, and that scopolamine impaired naive but not WM strategiespretrained rats (Beiko et al, 1997;Saber and Cain, 2003). We also found that combinations of either PRO and scopolamine, or pCPA and scopolamine impaired all aspects of WM performance in both naive and strategiespretrained rats, and also caused sensorimotor impairments (Beiko et al, 1997;Saber and Cain, 2003).…”
Section: Introductionsupporting
confidence: 74%
“…Our previous studies confirmed that neither PRO nor pCPA given individually impaired WM performance, and that scopolamine impaired naive but not WM strategiespretrained rats (Beiko et al, 1997;Saber and Cain, 2003). We also found that combinations of either PRO and scopolamine, or pCPA and scopolamine impaired all aspects of WM performance in both naive and strategiespretrained rats, and also caused sensorimotor impairments (Beiko et al, 1997;Saber and Cain, 2003). These 'global' cognitive/behavioral impairments due to combined antagonism of neurotransmitter systems known to be impaired in Alzheimer disease are consistent with the cognitive/ behavioral impairments seen in Alzheimer patients.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…with either 10 mg/kg of propranolol or saline and tested again 48 h later (Test 2). This dosage of propranolol is one of the highest previously used in several studies to interfere with the consolidation or reconsolidation in several different types of memories, including both aversive and appetitive (e.g., Sara et al 1995;Przybyslawski et al 1999;Saber and Cain 2003;Debiec and LeDoux 2004;Diergaarde et al 2006;Abrari et al 2007;Milton et al 2008;Rodriguez-Romaguera et al 2009). All groups of rats had similar retention latencies at Test 1 and Test 2.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas we cannot exclude that intracerebral administration of propranolol might affect IA reconsolidation, in the present study we chose to focus on systemic administrations, because our goal was to test for effects potentially relevant for clinical applications. Furthermore, the dose used in our studies is the same used in the majority of investigations that reported an effect of propranolol on memory consolidation and reconsolidation (e.g., Sara et al 1995;Przybyslawski et al 1999;Saber and Cain 2003;Debiec and LeDoux 2004;Diergaarde et al 2006;Abrari et al 2007;Milton et al 2008;Rodriguez-Romaguera et al 2009). A total of 10 mg/kg appears to be the highest dose that can be utilized systemically in rat without causing a toxic effect.…”
Section: Discussionmentioning
confidence: 99%